Harry Potter and the chamber of secrets - Rowling, J. K. (London : Bloomsbury, 2004)
When the Chamber of Secrets is opened again at the Hogswart School for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
5-8.
5-8
Keywords: Fantasy; Greek language materials; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Potter, Harry (Fictitious character) -- Fiction; Schools -- Fiction; Witches -- Fiction; Wizards -- Fiction; Greek language; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Potter, Harry (Fictional character) -- Fiction; School stories; Witches -- Fiction; Wizards -- Fiction; England -- Fiction; England -- Fiction; Fantastic fiction